PENGARUH HALAL CERTIFICATION DAN HALAL AWARENESS TERHADAP MINAT PEMBELIAN PRODUK GUNAAN - Lina Budiarti; Rena Feri Wijayanti; Tri Yulistyawati Evelina (Politeknik Negeri Malang, 2019)
This study aimed to determine the role of halal certification and halal awareness toward used product buying behavior. The data was collected by distributing questionnaires to 100 college students of State Polytechnic of Malang that are selected through purposive sampling technique. Data analysis techniques used in this study is the linear regression analysis. The study show that halal certification and halal awareness have positive impact on used product buying behavior.